2005
DOI: 10.1080/00420980500185389
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Commuting Distances in French Polycentric Metropolitan Areas: Paris, Lyon and Marseille

Abstract: It has frequently been suggested in the literature that a polycentric distribution of employment and people shortens commuting distances because people locate within or close to their employment sub-centre (the co-location hypothesis). Having studied the three biggest French metropolitan areas over the past decade it has been established that co-location affects only a minority of inhabitants, of whom there are fewer in 1999 than there were nine years earlier. Indeed, the majority of people living in a sub-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
26

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 29 publications
(34 reference statements)
1
104
0
26
Order By: Relevance
“…Some studies found that polycentric structures lead to lower average distances than monocentric structures (e.g. Gordon et al 1989;Song 1992;Guiliano and Small 1993;Spence and Frost 1995;Alpkokin et al 2008) whereas other studies found opposite results (Baccaini 1997;Cervero and Wu 1997;Ewing 1997;Schwanen et al 2003;Aguilera 2005). In their study on 50 metropolitan areas in the U.S., Yang et al (2012) found that the relation depends on the threshold of population density that is used to define polycentricity: high density polycentricity increases commuting times whereas moderate high-density polycentricity lengthens commuting times.…”
Section: Polycentricitymentioning
confidence: 82%
“…Some studies found that polycentric structures lead to lower average distances than monocentric structures (e.g. Gordon et al 1989;Song 1992;Guiliano and Small 1993;Spence and Frost 1995;Alpkokin et al 2008) whereas other studies found opposite results (Baccaini 1997;Cervero and Wu 1997;Ewing 1997;Schwanen et al 2003;Aguilera 2005). In their study on 50 metropolitan areas in the U.S., Yang et al (2012) found that the relation depends on the threshold of population density that is used to define polycentricity: high density polycentricity increases commuting times whereas moderate high-density polycentricity lengthens commuting times.…”
Section: Polycentricitymentioning
confidence: 82%
“…As in most metropolitan areas, several employment sub-centres have developed or gained in strength (Aguiléra, 2005). The biggest (in terms of total number of jobs) are located in the first crown and are close to the central city, in its surrounding municipalities, such as the La Défense business centre in the western part of the first crown.…”
Section: -1 Employment Suburbanisationmentioning
confidence: 99%
“…home to work journeys, have largely followed these general trends (Aguiléra, 2005;Alpkokin et al, 2008;Giuliano and Small, 1993;Shearmur, 2006). The suburbanisation of jobs and housing has thus led to the development of suburb-to-suburb commuting and reverse commuting, defined as home-to-work journeys from the central city to the outskirts (Christopher et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have concluded that this is the case, others have come to the opposite conclusion . For example, Clark and Kuijpers-Linde (1994) concluded that during the transition to a polycentric urban system in the Randstad there will be more congestion and increased commuting times (see also Aguilera 2005;Williams 2005).…”
Section: Literature Reviewmentioning
confidence: 99%